Population pharmacokinetics and pharmacodynamics of bivalirudin in young healthy Chinese volunteers - Zhang Dong-mei; Wang Kun; Zhao Xia; Li Yun-fei; Zheng Qing-shan; Wang Zi-ning; Cui Yi-min (Acta Pharmacologica Sinica; Vol 33, No 11 (November 2012): Acta Pharmacologica Sinica (Special Feature: Pharmacometrics), 2016)
Aim: To investigate the population pharmacokinetics (PK) and pharmacodynamics (PD) of bivalirudin, a synthetic bivalent direct thrombin inhibitor, in young healthy Chinese subjects. Methods: Thirty-six young healthy volunteers were randomly assigned into 4 groups received bivalirudin 0.5 mg/kg, 0.75 mg/kg, and 1.05 mg/kg intravenous bolus, 0.75 mg/kg intravenous bolus followed by 1.75 mg/kg intravenous infusion per hour for 4 h. Blood samples were collected to measure bivalirudin plasma concentration and activated clotting time (ACT). Population PK-PD analysis was performed using the nonlinear mixed-effects model software NONMEM. The final models were validated with bootstrap and prediction-corrected visual predictive check (pcVPC) approaches. Results: The final PK model was a two-compartment model without covariates. The typical PK population values of clearance (CL), apparent distribution volume of the central-compartment (V1), inter-compartmental clearance (Q) and apparent distribution volume of the peripheral compartment (V2) were 0.323 L·h-1·kg-1, 0.086 L/kg, 0.0957 L·h-1·kg-1, and 0.0554 L/kg, respectively. The inter-individual variabilities of these parameters were 14.8%, 24.2%, fixed to 0% and 15.6%, respectively. The final PK-PD model was a sigmoid Emax model without the Hill coefficient. In this model, a covariate, red blood cell count (RBC*), had a significant effect on the EC50 value. The typical PD population values of maximum effect (Emax), EC50, baseline ACT value (E0) and the coefficient of RBC* on EC50 were 318 s, 2.44 mg/L, 134 s and 1.70, respectively. The inter-individual variabilities of Emax, EC50, and E0 were 6.80%, 46.4%, and 4.10%, respectively. Conclusion: Population PK-PD models of bivalirudin in healthy young Chinese subjects have been developed, which may provide a reference for future use of bivalirudin in China.